Variation of Grip Strength and Wrist Range of Motion with Forearm Rotation in Healthy Young Volunteers Aged 23 to 30 - Fan, Stacy; Cepek, Jeremy; Symonette, Caitlin; Ross, Douglas; Chinchalkar, Shrikant; Grant, Aaron (Journal of Hand and Microsurgery, 2019)
Background Grip strength and wrist range of motion (ROM) are important metrics used to evaluate hand rehabilitation and outcomes of wrist interventions. Published normative data on these metrics do not recognize the contribution of forearm rotation. This study aims to identify and quantify variations in grip strength and wrist ROM with forearm rotation in healthy young individuals.Materials and Methods Wrist ROM and grip strength were measured in 30 healthy volunteers aged 23 to 30. Participant demographics, grip strength, and wrist ROM (wrist flexion and extension, ulnar and radial deviation) at three forearm positions (full supination, neutral, and full pronation) were measured using a digital dynamometer and standard goniometers. Data analysis was conducted using a one-way repeated measure ANOVA. Forearm position values were compared using post hoc analysis.Results Grip strength in males was greatest in neutral position (males: nondominant 51.4 kg, dominant 56.1 kg) followed by supination (males: nondominant 46.6 kg, dominant 51.7 kg) and weakest in pronation (males: nondominant 40.1 kg, dominant 42.9 kg). Grip strength in females was similar between supination (nondominant: 26.1 kg, dominant: 28.5 kg) and neutral (nondominant: 27.4 kg, dominant: 29.1 kg) positions, but both were greater than in pronation (nondominant: 22.3 kg, dominant: 24.1 kg). Wrist flexion in males was significantly reduced in supination compared with neutral and pronated positions (nondominant: supination 63.1°, neutral 72.6°, pronation 73.3°; dominant: supination 62.4°, neutral 70.2°, pronation 70.3°), whereas not significant wrist flexion in females was also weaker in supination (supination 74.4°, neutral 79.9°). Wrist extension in males was greater in pronation (supination 64.6°, pronation 69.5°) whereas females showed no significant difference in any of the forearm positions. Ulnar deviation in males did not differ with forearm position, but females demonstrated greater ulnar deviation in supination on the nondominant hand (supination 44.6°, pronation 33.2°). Whereas there was no difference in radial deviation with forearm position in females, it was markedly greater in pronation versus supination on both sides in males (nondominant: supination 16.3°, pronation 24.6°; dominant: supination 15.4°, pronation 23.9°).Conclusion This study characterizes variations in grip strength and wrist ROM in three forearm positions in healthy young individuals. All measurements differed with forearm rotation and were not influenced by hand dominance. These results suggest that wrist ROM and grip strength should be evaluated in different positions of forearm rotation, rather than a fixed position. This has functional implications particularly in patients involved with specialized activities such as sports, instrument-playing, or work-related activities.
Keywords: wrist motion; grip strength; functional range; rehabilitation